Weak-Type Inequality for Conjugate First Order Riesz-Laguerre Transforms - Forzani, Liliana Maria (2011)
In this paper we introduce a conjugate class of Riesz transforms in the context of Laguerre polynomials. We prove their weak-type (1,1) and Lp, 1